Business Success and Psychological Traits of Housing Developers - Jaafar, Mastura; Nuruddin, Azlan Raofuddin; Syed Abu Bakar, Syed Putra (UTS ePRESS, 2014)
Although the issues on entrepreneurship in the real estate industry are disparaging and have received little interest from global researchers, the significant roles played by the industry players warrant further investigation. The personal traits of the owners/managers are deemed to be the key factors to the business success of housing development firms. This paper examined the main determinants of successful businesses in the housing development sector under the lens of psychological traits of the owners/managers. To identify the success factors of housing development firms, interviews were conducted on 10 housing developers in Peninsular Malaysia. The study shows the significant psychological traits that distinguish the business success of housing developers compared with those in the existing literature. These factors are (1) high confidence and ambition, (2) vision and foresight, (3) industriousness, (4) perseverance and (5) integrity. As housing development is a risky industry, developers can use these findings as a guideline in managing their business toward superior performance.